Ventral Cervical Intradural Extramedullary Neuroenteric Cyst and its Operative Procedure; A Rare Case Report with Literature Review (Bangladesh Journal of Neurosurgery, 2022)
Background:Neuroenteric cysts are rare non-neoplastic lesions arising from a failure of dissolution of the transient neuroenteric canal between the foregut and the notochord. They are most frequently seen in the intraduralextramedullary space in the lower cervical and upper thoracic spine.Case description:A 5 yrs old boy presented to us with the complaints of neck and upper back pain and weakness of all four limbs. MRI scan shows an intraduralextramedullary cystic lesion at C6-T1 with significant compression over cord. After patient’s preparation a Posterior approach was used to remove the cysts. Post-operative course was un-eventful. Histological results were consistent with neuroenteric cysts. MRI image of 3 months follow-up shows no residual cysts and the boy has no further complaints.Conclusion:Neuroenteric cyst (NC) is a rare lesion usual location at lower cervical and upper dorsal area and should be considered among differential diagnoses. Complete excision is the treatment of choice. In most instances a dorsal surgical approach will be satisfactory.Bang. J Neurosurgery 2021; 11(1): 54-57